The Relationship Between Pregnancy Exercise And Quality Of Sleep For Pregnant Women In Trimester III At The Juliana Dalimunthe Clinic, Percut Sei Tuan Sub-District, Deli Serdang District, 2022 - Siregar, Eka Sylviana; Mawaddah, Maulina (Sean Institute, 2022)
Dealing with the problem of sleep disturbances in pregnant women, we can provide several methods to stabilize the quality of good sleep, such as determining a good and comfortable position during sleep, basic relaxation exercises, one of which is pregnancy exercise. This study aims to determine the relationship between Pregnancy Exercise and Sleep Quality for Pregnant Women in the Third Trimester. This type of research is a descriptive correlation research that aims to reveal the correlative relationship between variables using a cross-sectional approach. The population of this study were all third trimester pregnant women totaling 25 respondents. The sampling technique uses total sampling. The results of the research on pregnancy gymnastics conducted by third trimester pregnant women at the Juliana Dalimunthe Clinic were mostly performed poorly by 14 respondents (56.0%). The majority of sleep quality in third trimester pregnant women at the Juliana Dalimunthe Clinic is still poor as many as 15 respondents (60.0%). There is a significant relationship between pregnancy exercise and the sleep quality of third trimester pregnant women at the Juliana Dalimunthe Clinic, with a p value = 0.000 (p <0.05). The conclusion of this study is that the better the exercise during pregnancy, the better the sleep quality of third trimester pregnant women.